The wind in the willows - Grahame, Kenneth, 1859- (New York : Union Square Kids, 2024)
"Mole, Ratty, Toad, and Badger are four friends living in the Wild Wood. From racing in a motorcar to getting lost in the forest, their days are always full of high-energy hijinks and adventures. Today's young readers will be charmed by this story of friendship and generosity"--
Ages 6-8